The relationship between sex hormone levels and ocular surface parameters in girls with idiopathic central precocious puberty - Jiang, Wen; Yang, Lixia; Liang, Shuang (Frontiers in Endocrinology, 2024)
The study aimed to investigate the correlation between the change of sex hormone levels and ocular surface parameters in girls with idiopathic central precocious puberty(ICPP).Methods: Eighteen girls with ICPP and 18 age-matched normal girls participated in this study, all of the participants had undergone physical measurements, laboratory tests, imaging examination and ocular surface assessments.The Objective Scatter Index (OSI) in the ICPP group was significantly higher than in the control group (P = 0.031), girls with ICPP showed slightly lower MNITBUT compared to the normal control group, although this difference was not statistically significant. Bivariate analysis revealed a positive association between estradiol and OSI (r=0.383, P=0.021), Additionally, in the study population, both Luteinizing hormone (LH) and Follicle-stimulating hormone (FSH) were negatively correlated with Mean noninvasive tear breakup time (MNITBUT) (r=-0.359, P=0.031)( r=-0.357, P=0.032).In comparison with the normal control group, alterations in the OSI were observed in girls with ICPP. This alteration may be associated with an elevation in estrogen levels. Although there was a slight non-significant decrease in NITBUT in ICPP girls, the negative correlation between LH and FSH with MNITBUT suggests new perspective for further investigation.